Lesion‐directed screening to optimize skin cancer detection in dermatology practice: an observational study. (12th February 2021) - Mylle, S.; Verhaeghe, E.; Van Coile, L.; Van de Maele, B.; Hoorens, I.; Brochez, L.
Abstract: Background: Early detection of skin cancer is still a major challenge in dermatology practice today. While surveillance programs are offered to high‐risk patients, systematic total‐body examination (TBE) in the general population is not cost‐effective. In the past, we demonstrated that a lesion‐directed screening (LDS) in the general population delivered similar detection rates to TBE and was less time‐consuming. Objectives: To study whether a lesion‐directed early‐access consultation can optimize skin cancer detection in dermatology practice. Methods: In this observational study, we offered an early‐access consultation in patients contacting the dermatology department concerning 1 or 2 lesions of concern meeting predefined criteria. Results: 342 persons were seen at the dermatology department after triage by phone. Skin cancer detection rate was 13.2% (4.1% for melanoma). If advised/referred by a doctor skin cancer detection rate was 23.6% (9% for melanoma). With a history of skin cancer, detection rate was 24.3% (4.3% for melanoma). In patients with no referral and a negative history of skin cancer, detection rate was 7.7% (1.7% for melanoma), which is at least triple the rates reported by population‐based screening programs. In patients in whom the index lesion was benign, worry of having skin cancer had decreased significantly by the end of the consultation. Additional total‐body examination in these patients had low additional detection rate (0.5%) and a high number of unnecessary excisions (number needed to excise 13). Conclusions: An early‐access dermatology consultation for LDS after triage by phone resulted in high overall skin cancer and melanoma detection rates. Our data indicate that performing TBE is especially useful if the index lesion is suspicious. In addition to surveillance programs in high‐risk patients, LDS may be a way to optimize skin cancer detection in the general population and use available time more efficiently in daily dermatology practice.